Analisis gambaran radiologis suspek ameloblastoma tipe solid pada radiograf CBCT 3D - Farina Pramanik; Lusi Epsilawati; Yurika Ambar Lita; Erna Herawati (Ikatan Radiologi Kedokteran Gigi Indonesia, 2019)
Objectives: The aim of this case report is to provide further information on the radiological features of a solid type ameloblastoma suspected on a 3D CBCT radiograph. Case Report: A patient came referred by a dentist for CBCT 3D radiography with suspected clinical diagnosis of a maxillary anterior dentigerous cyst. The results of the CBCT 3D radiographic examination showed a radiointermediate with a clear border on the anterior maxilla and in the right maxillary sinus accompanied by the impact of two supernumerary teeth. Radiological features of ameloblastoma generally show a multilocular radiolucent picture and have a radiopaque septa bone internal structure such as a soap bubble appearance or honey combed appearance. This case showed a clearly demarcated radiointermediate image because a solid type ameloblastoma contains tissue that is histologically formed from cells hat are follicular or plexiform and derived from the results of a degenerative process at the center of the Langerhans islands. Conclusion: Radiographic examination with high modality such as CBCT 3D is very important in helping to establish a diagnosis, especially for cases that sometimes show differences in the radiographs.